Anti-Inflammatory Activity and Phytochemical Profile from the Leaves of the Mangrove Sonneratia caseolaris (L.) Engl. for Future Drug Discovery - Rozirwan; Ade Siswanto; Nadila Nur Khotimah; Redho Yoga Nugroho; Wike Ayu Eka Putri; Fauziyah; Rezi Apri; Hartoni (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
The increasing demand for effective and natural anti-inflammatory agents prompts an investigation into the properties of Sonneratia caseolaris (L.) Engl., a plant traditionally used in medicine. This study aimed to explore the ability of S. caseolaris leaves extract to inhibit inflammation and accelerate wound healing. S. caseolaris leaves were collected from Tanjung Api-Api area, Banyuasin, South Sumatra. The method involved carrageenan induction in rat paws as an inflammatory model. The results showed that the most effective dose was found in the group with a dose of 150 mg/kg BW measured using a digital caliper and plethysmometer. The qualitative phytochemical test contain alkaloids, steroids, flavonoids, and phenols. The results GC-MS analysis were thought to contain aldehydes, glucosinolates, coumarins, esters, terpenoids, alcohols, lipids, tocopherols, and steroids. Due to their diverse range of mechanisms of action, coumarins show significant promise in mitigating inflammation and hold potential for treating inflammatory conditions. This study provides new insights related to the potential of S. caseolaris as a source of natural anti-inflammatory agents, supporting public comprehension regarding the utilization of traditional herbal remedies.